Investigation of inter‐ and intra‐rater reliability using digital dental software for prosthodontics crown preparations. Issue 9 (22nd May 2020) - Shih, Wen; Tran, Kenny; Yang, Vivian; El Masoud, Bilal; Sexton, Christopher; Zafar, Sobia
Abstract: Introduction: Since the introduction of the digital dental assessment systems, there has been a shift towards this trend as it appears to provide a more accurate, reliable, time efficient, and reproducible assessment. The Planmeca Emerald scanner coupled with Romexis Compare software allows students and staff to objectively assess individual crown preparations, receive numerical values of key dimensions, and subsequently undergo comparison with ideal crown preparation dimensions. Objectives: To measure the inter‐ and intra‐rater reliability using the intra‐oral scanner and Romexis Compare for prosthodontic crown preparations, and to evaluate the possible implementation of this software as a grading and self‐assessment tool in a preclinical setting. Methods: The Planmeca scanner and Romexis Compare were used to compare the difference between 30 experimental preparations (n = 15 anterior teeth, n = 15 posterior teeth) with their respective unprepared typodont teeth. Three student examiners (W., K., V.) independently scanned the typodont teeth in pre‐formed standardized and non‐standardized putty jigs. Each preparation was measured from facial, lingual, incisal/occlusal, and margin surfaces. A second trial was completed after 2 weeks to assess intra‐rater reliability. The data were tabulated, graphed, and analyzed using SPSS and GraphPad Prism. Results: The results of the study show greater consistencies in inter‐operator measurements for anterior teeth. Some variations, however, were found in posterior teeth measurements between the operators. The results of the intra‐rater measurements appear to be relatively consistent. Conclusion: With some limitations, Romexis Compare can be used as a reliable and repeatable method for objective and consistent evaluation of student prosthodontic preparations in a preclinical setting.